Implementation of religious internalization activities in schools to shape Tahfiz students’ personality - Dzulkifli, Izuli; Mastor, Khairul Anwar; Yunos, Nasruddin; Syed Aziz, Sharifah Noorhidayah (Human Resources Management Academic Research Society (HRMARS), 2024)
Current tahfiz education no longer focuses solely on memorizing verses of the Quran. Tahfiz education also includes several subjects related to the Islamic religious and academic education. Tahfiz students would perform various physical and spiritual activities to strengthen their memorization of the Quran verses, as well as their personality in their daily life at school. This study aimed to explore the practices implemented by school administrators to strengthen the importance of personality among tahfiz students. This study utilized a semistructured interview method as an instrument to obtain data. Interviews were conducted with seven teachers representing school administrators from seven private tahfiz schools in Selangor. This study found that the tahfiz school administrators have implemented several activities, such as qiamullail (waking up at night), non-obligatory fasting, and practising several daily zikr to strengthen students’ personality. This study contributes by offering recommendations for curriculum and co-curriculum management to the tahfiz school administrators, which include the practice of religious internalization. This wholesome practice could improve the personality of the students, and help them achieve excellence in terms of faith, religious practices, and becoming virtuous characters.